Differences in Multimorbidity among Cisgender Sexual Minority and Heterosexual Adults: Investigating Differences across Age-Groups. (June 2021) - Caceres, Billy A.; Travers, Jasmine; Sharma, Yashika
Objectives: Despite increased risk for chronic disease, there is limited research that has examined disparities in multimorbidity among sexual minority adults and whether these disparities differ by age.Methods: Data were from the 2014–2018 Behavioral Risk Factor Surveillance System. We used sex-stratified multinomial logistic regression to examine differences in multimorbidity between sexual minority and heterosexual cisgender adults and whether hypothesized differences varied across age-groups.Results: The sample included 687, 151 adults. Gay, lesbian, and bisexual adults had higher odds of meeting criteria for multimorbidity than same-sex heterosexual adults. These disparities were greater among sexual minority adults under the age of 50 years. Only other non-heterosexual men over the age of 50 years and lesbian women over the age of 80 years were less likely to have multimorbidity than their same-sex heterosexual counterparts.Discussion: Health promotion interventions to reduce adverse health outcomes among sexual minorities across the life span are needed.